Program For Implementing Samsat Enrekang Motor Vehicle Tax Breaking Program For Taxpayers - Andi Arifwangsa Adiningrat; Nurhikmah Nurhikmah; Muhammad Khaedar Sahib; Andi Jam'an (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study is to find out the optimization of the motor vehicle tax bleaching program in increasing taxpayer compliance in paying taxes at the Samsat Enrekaang office. The research object of this Final Project is